Enhanced potency of bivalent small molecule gp41 inhibitors. Issue 1 (1st January 2017) - Sofiyev, Vladimir; Kaur, Hardeep; Snyder, Beth A.; Hogan, Priscilla A.; Ptak, Roger G.; Hwang, Peter; Gochin, Miriam
Graphical abstract: Highlights: Bivalent gp41 inhibitors were 40–60-fold more potent than monomers. Binding potency was not significantly improved by dimerization. Potency was correlated to slower off-rates. Data could be explained by a bidentate binding model for the dimers. The kinetic dependence may be due to transience of the targeted intermediate. Abstract: Low molecular weight peptidomimetic inhibitors with hydrophobic pocket binding properties and moderate fusion inhibitory activity against HIV-1 gp41-mediated cell fusion were elaborated by increasing the available surface area for interacting with the heptad repeat-1 (HR1) coiled coil on gp41. Two types of modifications were tested: 1) increasing the overall hydrophobicity of the molecules with an extension that could interact in the HR1 groove, and 2) forming symmetrical dimers with two peptidomimetic motifs that could potentially interact simultaneously in two hydrophobic pockets on the HR1 trimer. The latter approach was more successful, yielding 40–60 times improved potency against HIV fusion over the monomers. Biophysical characterization, including equilibrium binding studies by fluorescence and kinetic analysis by Surface Plasmon Resonance, revealed that inhibitor potency was better correlated to off-rates than to binding affinity. Binding and kinetic data could be fit to a model of bidentate interaction of dimers with the HR1 trimer as an explanation for the slow off-rate, albeit with minimal cooperativity due to the highly flexible ligand structures. The strong cooperativity observed in fusion inhibitory activity of the dimers implied accentuated potency due to the transient nature of the targeted intermediate. Optimization of monomer, dimer or higher order structures has the potential to lead to highly potent non-peptide fusion inhibitors by targeting multiple hydrophobic pockets.